A Directional Entropic Force Approach to Assemble Anisotropic Nanoparticles into Superlattices1. Issue 52 (7th November 2013) - Young, Kaylie L.; Personick, Michelle L.; Engel, Michael; Damasceno, Pablo F.; Barnaby, Stacey N.; Bleher, Reiner; Li, Tao; Glotzer, Sharon C.; Lee, Byeongdu; Mirkin, Chad A.
<x xml:space="preserve">Abstract</x> Not touching but sticking: By using cationic surfactant micelles as depletants, a directional entropic force approach (DEFA) assembles anisotropic nanoparticles into superlattices in solution. The micelles induce the face‐to‐face stacking of the nanoparticles to maximize the system's entropy. The shape of the nanoparticles determines the symmetry of the superlattice, the interparticle spacing is determined by the charged surfactant.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>